Development of model categories for performance improvement studies related to airportterminal operations - KC James and M Bhasi (Journal of Simulation (2009) 0, 1-11, 2009)
Simulation modelling has been widely used for the design and performance improvement of logistic terminal systems. One of the issues related to the performance improvement studies of airport terminal systems is the need for developing and using many different models of the same terminal system for solving its problems. A possible approach to address this difficulty is some form of problem clustering and model clustering, that is for the solution of problems from a problem category using corresponding models from the model category. In this paper, we discuss the conceptual modelling and development of three types of model categories called Fixed Facility Focus models, Variable Facility Focus models and Transient Entity Focus models and explain their use to solve problems of strategic nature related to fixed facilities, tactical problems related to the variable facilities, and operational problems related to transient entities and their schedules